2022
DOI: 10.1002/jcu.23119
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of second ultrasound‐guided fine‐needle aspiration for thyroid nodules

Abstract: Objective This study aimed to investigate the diagnostic value of doing a second ultrasound‐guided fine‐needle aspiration (US‐FNA) for thyroid nodules of different sizes that could not be diagnosed by the first US‐FNA. Methods One hundred and forty‐three patients (162 nodules) were diagnosed with suspected malignant thyroid nodules in a routine ultrasound examination, but since the diagnosis could not be confirmed by the cytology of the samples collected in the first US‐FNA, the patients underwent US‐FNA again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Currently, ultrasound-guided fine needle aspiration (US-FNA) remains the most effective and tolerable technique for diagnosing malignancy. 15 The Bethesda System for Reporting Thyroid Cytopathology (BSRTC) utilizes six categories for thyroid cytology reporting: I-nondiagnostic, II-benign, III-atypia of undetermined significance / follicular lesion of undetermined significance, IV-follicular neoplasm / suspicious for follicular neoplasm, V-suspicious for malignancy, and VI-malignant. 16 A study found that 44.77% (522/1166) of patients with a Bethesda II FNA underwent thyroid surgery, with incidental malignancy identified in 1.53% (8/522) of these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, ultrasound-guided fine needle aspiration (US-FNA) remains the most effective and tolerable technique for diagnosing malignancy. 15 The Bethesda System for Reporting Thyroid Cytopathology (BSRTC) utilizes six categories for thyroid cytology reporting: I-nondiagnostic, II-benign, III-atypia of undetermined significance / follicular lesion of undetermined significance, IV-follicular neoplasm / suspicious for follicular neoplasm, V-suspicious for malignancy, and VI-malignant. 16 A study found that 44.77% (522/1166) of patients with a Bethesda II FNA underwent thyroid surgery, with incidental malignancy identified in 1.53% (8/522) of these cases.…”
Section: Discussionmentioning
confidence: 99%